Alternative sources of phosphorus in beet production aiming at the organic system - Lucas Daniel Pimenta; Antonio Ismael Inacio Cardoso; Jolinda Mércia de Sá (Pesquisa Agropecuária Tropical, 2024)
The demand for beet produced in the organic system has increased. This study aimed to evaluate the beet production with the use of different proportions of phosphorus sources. A randomized block design was used. The treatments were established in a 6 x 2 + 1 factorial arrangement, corresponding to 6 proportions of the phosphorus fertilizers Yoorin®thermophosphate (YT) and bone meal (BM) (100 % of P2O5 with YT; 80 % of P2O5 with YT + 20 % of P2O5 with BM; 60 % of P2O5with YT + 40 % with BM; 40 % of P2O5 with YT + 60 % with BM; 20 % of P2O5 with YT + 80 % with BM; and 100 % of P2O5 with BM), 2 doses of P2O5 (180 - recommended - and 360 kg ha-1) and 1 control without these phosphorusfertilizers. The plant height, number of leaves, root and shoot fresh and dry weight, transverse and longitudinal root diameter and total root yield were evaluated. The recommended fertilizer dose resulted in higher values, when compared to twice the recommendation. The proportion of 0 % of thermophosphate and 100 % of bone meal provided the highest mean values for the evaluated parameters. High phosphorus doses showed to be harmful to beet production.